Characteristics of Active Tuberculosis Patients Requiring Intensive Care Monitoring and Factors Affecting Mortality - (:unkn) unknown (TAEHAN KYORHAEK HYOPHOE-KOREAN ACAD TUBERCULOSIS & RESPIRATORY DISEASES, 2016)
Background: One to three percent of cases of acute tuberculosis (TB) require monitoring in the intensive care unit (ICU). The purpose of this study is to establish and determine the mortality rate and discuss the causes of high mortality in these cases, and to evaluate the clinical and laboratory findings of TB patients admitted to the pulmonary ICU. Methods: The data of patients admitted to the ICU of Yedikule Chest Diseases and Chest Surgery Education and Research Hospital due to active TB were retrospectively evaluated. Demographic characteristics, medical history, and clinical and laboratory findings were evaluated. Results: Thirty-five TB patients (27 males) with a median age 0117 years were included, of whom 20 died within 30 days (57%). The Acute Physiology and Chronic Health Evaluation 11 (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores were significantly higher, and albumin and PaO2/FIO2 levels were significantly lower, and shock, multiple organ failure, the need for invasive mechanical ventilation and drug resistance were more common in the patients who died. The mortality risk was 7.58 times higher in the patients requiring invasive mechanical ventilation. The SOFA score alone was a significant risk factor affecting surviVal Conclusion: The survival rate is low in cases of tuberculosis treated in an ICU. The predictors of mortality include the requirement of invasive mechanical ventilation and multiple organ failure. :Another factor specific to rt B patients is the presence of drug resistance, which should be taken seriously in countries where there is a high incidence of the disease. Finding new variables that can be established with new prospective studies may help to decrease the high mortalit\ rate.
Keywords: Tuberculosis; Respiratory Insufficiency; Critical. Care; ACUTE RESPIRATORY-FAILURE; PULMONARY TUBERCULOSIS; MECHANICAL VENTILATION; RETROSPECTIVE COHORT; UNIT; PROGNOSIS; KOREA